The interaction between exercise induced muscle damage and fatigue on neural regulation and exercise performance during submaximal and maximal running - Noel, Colin Byron (Department of Surgery, 2019)
Aim: To study the effects of muscle damage and fatigue on neuromuscular preactivation and performance during submaximal and maximal running. Setting: University of Cape Town, Sports Science Institute of South Africa. Methods: 12 male distance runners (19 - 39 years of age) with a minimum weekly training distance of 40 kilometers per week were randomly assigned to either control (n = 6) or experimental (n = 6) groups. Subjects’ visited the laboratory over an 11 day period during which testing included a submaximal and maximal run (5 km time trial) on the first and last day of testing. Neuromuscular preactivation, rating of perceived exertion, heart rate and performance times were recorded during the performance trials. The intervention between performance trials included two 40 minute bouts on a treadmill at 70 % peak treadmill running speed at –10 º elevation (experimental) or horizontal (control). Results: Running performance in the 5 km time trial (5K) improved in the experimental group alone by an average of 40 seconds over 5 km (P < 0.04) in the presence of muscle damage and without altered neuromuscular preactivation. There was no evidence any interaction between altered neuromuscular activity with regard to fatigue and muscle damage during submaximal and maximal running. Evidence of muscle damage in the experimental group was supported by a significant group versus time interaction effect in subjective pain score for daily living and increased plasma creatinine kinase levels in the experimental group (P<0.03). A significant decrease in rating of perceived exertion (RPE) was observed in both groups during both the submaximal (P<0.04) and 5 km time trial (P<0.03) post intervention. There was an interaction effect for group versus pre-post 5K (P<0.06), with the post 5K RPE in the experimental group showing an average decreased RPE score of 2.6 for each kilometer and the control group an average decrease in RPE score of only 0.03. Conclusion: The research design of this study was appropriate to study the interaction between fatigue and muscle damage during submaximal and maximal running. This study suggests that there is no neuromuscular compensation after muscle damage and that EMG is regulated similarly for both fatigue and muscle damage during submaximal and maximal running. Improvement in running performance and decreased rating of perceived exertion after muscle damage is due to some unknown variable.